2022
DOI: 10.1037/edu0000714
|View full text |Cite
|
Sign up to set email alerts
|

Fraction ball: Playful and physically active fraction and decimal learning.

Abstract: to the design and implementation of the study, as well as analyses and preparation of the manuscript.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Our previous research found an association between more frequent parent conversation (during share television viewing) and higher kindergarten curiosity, with a greater magnitude of association in children from low-SES families (Shah et al, 2021). Research from Playful Learning Landscapes including Urban Thinkscape and other projects like Parkopolis (Bustamante et al, 2020); a life-sized human board game) and Fractionball (Bustamante et al, 2022); a recrafted basketball court designed to promote fraction talk) demonstrate that transforming neighborhood spaces into areas which prioritize caregiver-child interactions, facilitate language-learning opportunities which are promotive of school 10.3389/fpsyg.2023.986221 readiness and question asking-a behavior associated with curiosity. Transforming neighborhoods into safer, more playful spaces can also lead to the promotion of early childhood curiosity by cultivating opportunities to engage in back and forth pedagogical exchanges, (e.g., "Look at this!…”
Section: Neighborhood Spaces As a Modifiable Ecological Context To Fo...mentioning
confidence: 94%
“…Our previous research found an association between more frequent parent conversation (during share television viewing) and higher kindergarten curiosity, with a greater magnitude of association in children from low-SES families (Shah et al, 2021). Research from Playful Learning Landscapes including Urban Thinkscape and other projects like Parkopolis (Bustamante et al, 2020); a life-sized human board game) and Fractionball (Bustamante et al, 2022); a recrafted basketball court designed to promote fraction talk) demonstrate that transforming neighborhood spaces into areas which prioritize caregiver-child interactions, facilitate language-learning opportunities which are promotive of school 10.3389/fpsyg.2023.986221 readiness and question asking-a behavior associated with curiosity. Transforming neighborhoods into safer, more playful spaces can also lead to the promotion of early childhood curiosity by cultivating opportunities to engage in back and forth pedagogical exchanges, (e.g., "Look at this!…”
Section: Neighborhood Spaces As a Modifiable Ecological Context To Fo...mentioning
confidence: 94%
“…By creating design that makes learning benefits salient for parents [ 108 ]. For example, drawing fraction lines on a basketball court ( Figure 2 ) may make it salient to parents that children are learning mathematics while playing [ 143 ]. Excitingly, not only does such design make learning benefits visible for parents and teachers, a controlled study showed that it actually does increase children’s understanding of fractions [ 143 ].…”
Section: Design Principlesmentioning
confidence: 99%
“…Number lines can be presented in multiple formats to illustrate fraction magnitude: (a) three-dimensional, concrete representations such as fraction bars and rulers; (b) two-dimensional, semi-concrete representations including drawings of number lines and pictures of rulers; and (c) virtual number lines on a screen (e.g., the free platform Math is Fun provides a digital fraction number line students can manipulate to explore equivalent fractions) or as a mental image in one’s head (Fuchs et al, 2021). A unique format example is a walkable fraction number line displayed on the ground that engages students in a whole-body, multimodal fraction learning experience (Bustamante et al, 2022). Concrete number line representations can be beneficial for early learners or those impacted by LD in mathematics followed in complexity by two-dimensional, semi-concrete number line illustrations.…”
Section: Key Recommendations For Planning and Implementing Fraction N...mentioning
confidence: 99%